(untitled) (Tikrit Journal of Pharmaceutical Sciences, 2023)
Pediatric ophthalmic disorders are important because of their impact on child’s development, education, future work, opportunities and quality of life, they may be due to causes that operate in prenatal period , neonatal period and childhood. This study aimed to determine the pattern of childhood eye diseases across age group among children attending out Patient eye department of Tikrit Teaching Hospital. It is a descriptive cross sectional study carried out in out Patient eye department of Tikrit Teaching Hospital .From 1st January 2010 to the end of December 2010.In this study 846 children at the ages up to 15 years were examined. A questionnaire was designed for recording personal history and detailed ocular clinical examination was done. A total of 846 children had attended the eye out patient during 2010.469(55.4%) were male and 377(44.5%) were female. Allergic conjunctivitis 229(27%),refractive error 124(14.6%), Ocular trauma 117(13.8%),infection108(12.7%),squint103(12.1%) and NLD obstruction 44(5.2%) were the most common conditions. Ocular injury was more common in males 67% and children aged 6-10 years 40%, the majority 65% being closed globe injury. Infections were seen more commonly among males 61% and children aged less than 5 years, with keratitis representing 33% of these cases. Conjunctivitis was the most common disorder followed by refractive error. Male were more commonly affected than female. Children aged 11-15 years made up largest group that affected. The prevalent childhood eye diseases can lead to absenteeism from school and are potentially blinding. Health education is important for parents to prevention of childhood eye injuries and early treatment of eye disorders.